GOLD AND GOLD-BEARING DEPOSITS OF THE WORLD: GENESIS AND METALLOGENIC POTENTIAL - Safonov Yu.G. (My University, 2003)
World gold production increased during the last century by more than five times, from approximately 500 to 2544 t in 2000. The shares of gold-only and complex gold-bearing deposits in these values are almost equal. The fall in gold production in the Witwatersrand deposit, with the main reserves of complex Au-U ores, and the simultaneous increase in production of gold from porphyry copper, massive sulfide, and gold-uranium-copper deposits resulted in the fact that, by the end of the last century, approximately 30% of gold was produced from complex deposits. The proportion of these deposits for gold reserves and production is increasing, similarly to that of epithermal Au-Ag mineralization. Of the 150-160 t of gold produced annually in Russia, 10-12% is a by-product metal. The distribution of large (≥100 t of Au) and superlarge (≥500 t), including giant (≥1000 t), gold deposits is controlled by geodynamic settings of three main types: (1) marginal continental belts, (2) volcanic arcs and belts (including greenstone belts), and (3) epicratonic basins and provinces of tectonic activation. The study of the Witwatersrand gold-bearing reefs implies their exhalation-sedimentary origin and a decisive role of gas emanations in concentration of gold in the near-surface zone of the Earth's crust. The pebble-conglomerate pattern of the reefs is explained by the colloidal mechanism of mineral deposition, crystallization, and disintegration. The formation of deposits with different mineralogical-geochemical specializations is determined by the geodynamic conditions of formation and evolution of fluid and fluid-magmatic ore-forming systems differing in depth, duration of activity, and gold ore productivity.